2001
DOI: 10.1002/app.1832
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of dye wastes by poly(vinyl alcohol)/poly(carboxymethyl cellulose) blend grafted through a radiation method

Abstract: The instability in water of poly(vinyl alcohol) (PVA)/poly(carboxymethyl cellulose) (CMC) was improved through radiation‐induced grafting with a styrene monomer. The PVA/CMC blend graft copolymer was used as a sorbent for dye wastes normally released from textile factories. The factors that may affect the sorption process such as time, temperature, weight of the blend graft copolymer, and volume of the dye waste were investigated. The sorption of dyestuffs by the blend graft copolymer was determined by a metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…Due to these reasons the dye concentration in the discharged water should be controlled. Grafted polymers were also tested in dye removal and grafted cellulose with appropriate functional groups was found to be a good sorbent (El-Hilw, 1999;El-Salmawi et al, 2001;Bouzaida and Rammah, 2002;Sokker et al, 2004;Aly et al, 2005;Hashem et al, 2005;Gupta and Suhas, 2009). When the binding to the grafted material takes place with weak forces, the uptake may be reversible and during solvent regeneration the dye is collected in concentrated solution.…”
Section: Adsorption Of Substances Other Than Heavy Metal Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to these reasons the dye concentration in the discharged water should be controlled. Grafted polymers were also tested in dye removal and grafted cellulose with appropriate functional groups was found to be a good sorbent (El-Hilw, 1999;El-Salmawi et al, 2001;Bouzaida and Rammah, 2002;Sokker et al, 2004;Aly et al, 2005;Hashem et al, 2005;Gupta and Suhas, 2009). When the binding to the grafted material takes place with weak forces, the uptake may be reversible and during solvent regeneration the dye is collected in concentrated solution.…”
Section: Adsorption Of Substances Other Than Heavy Metal Ionsmentioning
confidence: 99%
“…Poly(vinyl alcohol)/carboxymethyl cellulose blend grafted by styrene in order to strengthen the stability of the blend was also tested for dyes sorption (El-Salmawi et al, 2001). High sorption affinity was found for the collection of basic, acidic and reactive dyes.…”
Section: Adsorption Of Substances Other Than Heavy Metal Ionsmentioning
confidence: 99%
“…PVA films have high mechanical strength and long-term temperature stability [11]. These properties of PVA have to led their use in several biomedical and industrial applications including contact lenses [12], ophthalmic materials [13], tendon repair [14], as sorbents for dye wastes [15,16], as sensors [17] and drug delivery system [18]. Some chemical hydrogels based on PVA are well known in literature [19].…”
Section: Introductionmentioning
confidence: 99%
“…Although extensive research work has been carried out on the synthesis and application of polymeric materials in the field of treatment of waste waters, few authors were concerned with PVA/poly(carboxymethyl cellulose) (CMC) polymer blends. It has been reported that the introduction of 6-16% of CMC Na salt to the PVA matrix leads to an increased sorption capacity with respect to water vapor [18].…”
Section: Introductionmentioning
confidence: 99%